COMPARISON OF VAGAL MANEUVERS VS VERAPAMIL FOR CARDIOVERSION OF ATRIOVENTRICULAR NODAL REENTRANT TACHYCARDIA. A COMPARATIVE CROSS SECTIONAL STUDY - Hadi, Noor ul; Asfandiyar; ullah, Ikram; Shah, Syed Tahir; Ahmad, Farooq; Rahman, Abdur; Ahmad, Mushataq (Journal of Ayub Medical College Abbottabad, 2021)
Background: Vagal Maneuver is an underutilized strategy for Cardioversion of Atrioventricular nodal reentrant tachycardia. The present study is an attempt to explore the effectiveness of this strategy. Methods: This comparative cross-sectional study was performed at the Department of Cardiology MTI MMC Mardan from the first January 2017 to 31 December 2019. Patients with Palpitations and having documented AVNRT on ECG were selected for this study. Patients were divided into two groups, i.e., Group A and Group B through envelope method. Patients in Group A were subjected to vagal maneuvers like carotid sinus massage, and Valsalva methods. Patients in Group B received injection verapamil 5 mg. Results: A sample size of 100 patients were enrolled. The mean age was 31 with 8.6SD. Male were 54% and females were 46%. The success rate of vagal maneuvers in group A was 36% (n=18), while in group B, it was 84% (n=42) for verapamil (36% vs 84%, p-value<0.001, highly significant). In group A, time for cardioversion in less than 2 minutes was 68%. While in group B, the time for cardioversion in less than two minutes was 12%. ( 68% vs 12%, p<0.001, highly significant).Cross over in Group A was 64% (n=32) to verapamil. While in group B, this was 6% (n=3) to DC shock and 14% (n=7) to vagal maneuvers (64% vs 18%, p<0.001, highly significant.) Conclusion: Simple Valsalva Maneuvers and verapamil proved to be effective in cardioversion of SVT/AVNRT. Both are safe. Verapamil is more successful in cardioversion as compared to Valsalva maneuvers.